2019
DOI: 10.5688/ajpe7013
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Continuing Professional Development Course in a Longitudinal Didactic Curriculum for Pharmacy Students

Abstract: Objective. To implement a continuous professional development (CPD) program in the didactic curriculum of a three-year Doctor of Pharmacy (PharmD) program, and evaluate associated outcomes. Methods. The initial CPD program was implemented in the didactic curriculum of the PharmD program in 2014-2015. Barriers were identified and strategies adopted to overcome the barriers. A revised CPD curriculum was implemented in the 2015-2016 academic year. Student and faculty evaluations of the course were conducted, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
(14 reference statements)
0
11
2
Order By: Relevance
“…CV development is an important ability closely linked to CPD, as also emphasized by Dyke JE et al's study. Students were made to comprehend how the CPD can contribute toward a unique CV for each student [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CV development is an important ability closely linked to CPD, as also emphasized by Dyke JE et al's study. Students were made to comprehend how the CPD can contribute toward a unique CV for each student [17].…”
Section: Discussionmentioning
confidence: 99%
“…As a student expressed in the focus group session, that now they can improve themselves in all elds: "now we also might improve ourselves not only in a community pharmacy, we could work also in other sectors". CPD allows students to individualize aspects of their education [17] since being a self-directed lifelong learner requires skills for determining individual learning needs. The students re ected on how they liked that the course was based on individual learning needs: "in university things are not based on our weakness or need we are never asked this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model in line with the Kolb's Cycle in which an effective learning requires the learner to progress through the cycle of concrete learning, re ective observation, abstract conceptualization and active experimentation [17]. Few studies reported implementing such a longitudinal program in pharmacy schools, namely, the Roseman University College of Pharmacy (RUCOP) longitudinal CPD program for a cohort of PharmD students in the US [18] and the tra c light report (TLR) program implemented within a Bachelor's of Science (BSc) in pharmacy curricula as an elective course in an Australian university [19].…”
Section: Introductionmentioning
confidence: 96%